The role of place branding in promoting social capital in urban areas (case study: Ahvaz, Iran) - Ramezi, Mansour; Yeganeh, Mansour; Bemanian, Mohammadreza (Frontiers in Built Environment, 2022)
The aim of this study is to investigate the impact of neighborhood branding in increasing its social capital. The issue of social capital at the neighborhood scale is one of the most important components of quality and for achieving various aspects of sustainability in human life in urban societies. Examining the background of this issue shows that paying attention to the potential of place branding as an essential and effective component in increasing the social capital in neighborhoods has not been seriously studied. This study aims to know the components and measures of place branding that can significantly impact increasing social capital. The conceptual model of this research has been tested in 13 neighborhoods of Ahvaz city and using the opinions of 663 residents of these neighborhoods. The research results show that social capital in neighborhoods is directly related to the brand of those neighborhoods. This study is limited to metropolises with diversity of architecture and diversity of texture and social structure in Iran. The results show that place branding with a coefficient of 0.77 has the highest impact on social values. The impact of place branding on social solidarity, social security, social participation, and place-belonging is equal to 0.61, 0.55, 0.39, and 0.33, respectively.